Korelasi Tipe Kusta dengan Keberhasilan Pengobatan di Sulawesi Tenggara - Hariati Lestari (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2024)
Leprosy remains a global health issue, with Indonesia ranking third in the world after India and Brazil. In Southeast Sulawesi, leprosy prevalence has increased over the past five years, with a new case detection rate of 8.45 per 100,000 population in 2022. This study aims to analyze the relationship between the types of leprosy, Paucibacillary (PB) and Multibacillary (MB), and the treatment success rate in Southeast Sulawesi from 2018 to 2022. This research employs an observational study with a correlation approach. Secondary data were obtained from the 2024 Southeast Sulawesi Provincial Health Profile. Data analysis was conducted using univariate and bivariate analysis with Pearson correlation tests. The results showed that the treatment success rate for MB leprosy increased from 77.20% in 2020 to 87.76% in 2022, while PB leprosy treatment success decreased from 85.71% to 70.27% over the same period. A significant relationship was found between the number of PB and MB leprosy cases and treatment success rates (p < 0.05). These findings indicate that the higher the number of leprosy cases, the higher the treatment success rate. This study is expected to serve as a basis for more effective leprosy control programs in Southeast Sulawesi